ORGANIC CERTIFICATION: CHALLENGES AND BENEFITS FOR PRODUCERS - Baldin, Antonio Mauricio (Revista Sistemática, 2022)
The pursuit of organic certification has become increasingly significant for agricultural producers seeking to meet growing consumer demand for sustainable and health-conscious food products. This certification verifies compliance with rigorous standards that prohibit synthetic inputs and genetically modified organisms, fostering transparency and trust in the organic market. However, producers face various challenges in the certification process, including high costs, complex regulatory requirements, transition periods with reduced yields, and limited technical support—especially for small-scale and developing country farmers. Despite these obstacles, organic certification offers substantial benefits, such as access to premium markets, product differentiation, and opportunities to promote social equity and environmental sustainability. Government policies and participatory certification models play crucial roles in mitigating barriers and supporting broader adoption. Addressing the economic, technical, and institutional challenges is essential to ensure inclusive growth of the organic sector worldwide.